2011
DOI: 10.1136/medhum-2011-010044
|View full text |Cite
|
Sign up to set email alerts
|

The arts and medicine: a challenging relationship

Abstract: This paper discusses various justifications for including medical humanities and art in healthcare education. It expresses concern about portrayals of the humanities and art as benign and servile in relation to medicine and the health professions. An alternative is for the humanities to take a more active role within medical education by challenging the assumptions and myths of the predominant biomedical model. Another is to challenge quiescent notions of the arts by examining examples of recent provocative wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 38 publications
0
32
0
1
Order By: Relevance
“…This theme perhaps saw the arts occupy their traditional role in medical education, whereby the arts are used as instruments to help develop such qualities as reflection, communication skills, critical thinking, leadership, access to tacit knowledge, empathy, appreciation of complexity and communities of practice in a variety of different groups that included undergraduate medical students, general practice trainees, teaching faculty staff, and mental health workers and their clients. Other studies suggested that using the visual arts in teaching can improve medical students’ observational and diagnostic skills …”
Section: Resultsmentioning
confidence: 99%
“…This theme perhaps saw the arts occupy their traditional role in medical education, whereby the arts are used as instruments to help develop such qualities as reflection, communication skills, critical thinking, leadership, access to tacit knowledge, empathy, appreciation of complexity and communities of practice in a variety of different groups that included undergraduate medical students, general practice trainees, teaching faculty staff, and mental health workers and their clients. Other studies suggested that using the visual arts in teaching can improve medical students’ observational and diagnostic skills …”
Section: Resultsmentioning
confidence: 99%
“…ii This is robustly posed as the claim that the medical humanities “do not merely have usefulness in contributing to the development of an ends other than themselves: they also have an intrinsic value in their own right and as such are essential components of the educated mind” 1. Macneill articulates the same sentiment when he expresses unease about “portrayals of the humanities and art as benign and servile in relation to medicine and the health professions”, which he apprehends as the “concern that the humanities and arts are used as mere instruments to the end of producing effective practitioners” 11. He continues,

The allusion here to Kant's categorical imperative (that we should not use another human being ‘merely as a means’ to our own ends) is deliberate as it helps to isolate what it is about the instrumental justification that is troubling.

…”
Section: The Standard Defence Of the Medical Humanitiesmentioning
confidence: 98%
“…Finally (and most prominently), it is asserted that the humanities can foster improvements in doctor–patient interactions by enhancing awareness of patienthood (through augmenting levels of empathy and moral sensitivities, and by improving bedside manner). While it should be reiterated that there is still scattered disagreement about whether these educational outcomes are realised by a medical humanities education,9 10 the foregoing provides a widely cited register of instrumental benefits that are both explicitly (and occasionally implicitly) alluded to in medical humanities and medical education literature 1–8 11 12…”
Section: The Standard Defence Of the Medical Humanitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…By using these newer, less pre-digested bodies of work, both students and teachers would find themselves in uncharted waters, with neither having any certainty about where their shared journey would end. 4 In the final paper in this series, John Harley Warner examines the way in which medical history has been co-opted to the service of scientific medicine for more than a century. Over this period of time, "the meanings attached to 'humanism' were both multiple and changing, and the role envisioned for history in a humanistic intervention was transformed".…”
Section: Deborah Kirklinmentioning
confidence: 99%